Analysis of the payment habits in Malta - Charles Saliba; Mary Ann Muscat (Central Bank of Malta, 2020)
This paper presents an extensive analysis on the means of payment that consumers in Malta use to purchase different goods and services. The aim of this study is to shed light on consumers' payment behaviour and in particular to improve the understanding of the considerations that shape consumers' payment choices, based on a survey of 500 households in Malta. Thus, it delivers essential information that should help the Central Bank of Malta and relevant payment systems stakeholders enhance their policies and strategic decisions with a view to improve the efficiency of the cash cycle and the payment systems more generally. Where possible, data are compared with the results of a 2013s survey on the same subject and also with statistics on the use of cash by households in the euro area.
Keywords: E41; E58; 330; payment habits; cash; consumer choice